2013
DOI: 10.1039/c2nr33347c
|View full text |Cite
|
Sign up to set email alerts
|

Excellent catalytic effects of highly crumpled graphenenanosheets on hydrogenation/dehydrogenation of magnesium hydride

Abstract: Highly crumpled graphene nanosheets (GNS) with a BET surface area as high as 1159 m(2) g(-1) was fabricated by a thermal exfoliation method. A systematic investigation was performed on the hydrogen sorption properties of MgH(2)-5 wt% GNS nanocomposites acquired by ball-milling. It was found that the as-synthesized GNS exhibited a superior catalytic effect on hydrogenation/dehydrogenation of MgH(2). Differential Scanning Calorimetry (DSC) and isothermal hydrogenation/dehydrogenation measurements indicated that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
39
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 118 publications
(44 citation statements)
references
References 49 publications
4
39
1
Order By: Relevance
“…It is found that there are two or three endothermic peaks for these samples. The identification of multiple peaks may be due to multimodal particle size distribution formed during milling as has been previously reported in the literature [15,16]. For the pure MgH 2 milled for 6 h, the dehydrogenation peak temperatures are 429 C and 450 C, respectively, while for the milled MgH 2 -G samples, their dehydrogenation peak temperatures shift to the much lower ones with increasing milling time except for the highest peak.…”
Section: Dehydrogenation Propertiessupporting
confidence: 66%
See 1 more Smart Citation
“…It is found that there are two or three endothermic peaks for these samples. The identification of multiple peaks may be due to multimodal particle size distribution formed during milling as has been previously reported in the literature [15,16]. For the pure MgH 2 milled for 6 h, the dehydrogenation peak temperatures are 429 C and 450 C, respectively, while for the milled MgH 2 -G samples, their dehydrogenation peak temperatures shift to the much lower ones with increasing milling time except for the highest peak.…”
Section: Dehydrogenation Propertiessupporting
confidence: 66%
“…Noticeably, G has also been confirmed to be an excellent catalyst on hydrogen desorption and adsorption of MgH 2 [15e17]. For example, Yuan et al [15] fabricated highly crumpled GNS (graphene nanosheets) and investigated the hydrogen sorption properties of MgH 2 -5 wt%GNS nanocomposites prepared by ball milling. It was found that the GNS exhibited a superior catalytic effect on hydrogenation/dehydrogenation kinetics of MgH 2 .…”
Section: Introductionmentioning
confidence: 99%
“…[32][33][34][35] Plotting ln[−ln(1−α)] against ln t in the range 0.2 α0.5 yields a straight line, where ƞ = slope and k = e intercept/slope . A hydrogen desorption fraction ranging from 0.2-0.5 was adopted to fit the kinetic curves.…”
mentioning
confidence: 99%
“…The barrier is lowered to 1.05 ev and the atomic hydrogen is also diffuse easily into the sublayer through the channels [92] due to which hydrogen dissociation/recombination in presence of GNS is facilitated and possible below 300°C. Liu et al [91]. clearly demonstrated that the small GNS dispersed in an irregular and disorderly manner in the composite after ball milling.…”
Section: Catalytic Effect Of Graphene On Sorption Behavior Of Mg/mghmentioning
confidence: 99%
“…Recently, the catalytic effect of graphene on sorption behavior of MgH 2 was reported by Liu et al [91]. They investigated the catalytic effect of graphene nanosheets (GNS) on the improvement of sorption behavior of MgH 2 .…”
Section: Catalytic Effect Of Graphene On Sorption Behavior Of Mg/mghmentioning
confidence: 99%